UPAYA PENINGKATAN KUALITAS HIDUP LANSIA DENGAN SENAM KAKI, AKUPRESUR DAN HOME CARE MELALUI POSBINDU - Martaulina Sinaga; Adelina Sembiring; Zuraidah Zuraidah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
Based on data from Riskesdas 2018, which states that the most common diseases in the elderly are Non-Communicable Diseases (PTM), such as hypertension, arthritis, stroke, Chronic Obstructive Pulmonary Disease (COPD) and Diabetes Mellitus (DM). In addition to having an impact on the physical condition of the elderly, the aging process also has an impact on their psychological condition. Improving health services for the elderly is needed to realize healthy, quality, and productive elderly in their old age. Health services for the elderly must be provided early on, namely at the pre-elderly age (45-59 years). One of the methods of implementing demgam is to carry out health development for the elderly, one of which is by taking preventive measures with foot exercises, acupressure and home care. Therefore, the target of this community service activity is the elderly who live in Simalingkar B Village, Medan Tuntungan District. The number of elderly who participated in this activity was 30 elderly. This activity was carried out for 2 days consisting of four vital signs examinations, two foot exercises and two times of acupressure. The implementation of this activity is the STIKes Mitra Husada Medan Nursing Study Program. The results of the activity evaluation show that foot exercises, acupressure and vital signs are routine activities carried out in Simalingkar B Village, Medan Tuntungan District. Through routine vital sign checks, it can control the health quality of the elderly. In addition, this activity can be a preventive measure against the symptoms of diseases that often occur in the elderly.